Hope as fundamental human response to loss and grief experiences in the time of COVID-19 - Gopez, Jose Ma W (J Public Health (Oxf), 2021)
The COVID-19 pandemic has forced changes in almost every aspect of human life, including the process of grieving. Due to strict safety measures, the grieving experience of the bereaved becomes more overwhelming and challenging. In this testing time, Gabriel Marcel’s ideas on hope can be a fundamental response to loss and grief. In situations wherein despair is experienced, responding with hope can help us cope with the complicated process of grieving.